Protein synthesis by fermentation of sugar cane added with urea and lactic acid culture - Ley-de Coss, Alejandro (2023)
The aim of this study was to evaluate the crude protein (CP) and true protein (TP) content of sugarcane after the solid-state fermentation process (SSF) with and without addition of urea or an inoculum of Pediococcus acidilactici, Lindner. Nine aerobic silos were used where three treatments were evaluated: ground whole cane (GWC), GWC plus 2% urea (GWCu) and GWC inoculated with 108 CFU of P. acidilactici (GWClab). pH, CP and TP levels were measured, as well as changes in the microbial populations. The pH was higher than 6.1, except for GWCu where it was lower (5.6; p<0.05). The amounts of CP and TP were low, without differences between treatments until the end of the incubation period (72 h). Low amounts of lactic acid bacteria (lab) were observed in GWCu, with no significant differences in GWC and GWClab (p>0.05). In the periods of 48 and 72 h, the number of cellulolytic and total bacteria were similar (p>0.05) between treatments. The FES of sugarcane allows to conserve forage, but in the short term it does not improve the content of CP and TP in the dry matter (DM), even with the addition of probiotics or urea.